HISTORY OF MAQOM ART AND ITS DEVELOPMENT (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article deals with the role of Asian peoples in the world science culture and art, and the history of Uzbek makomlik art and its development stages.